A discourse analysis of advertisements in english and vietnamese on the internet (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is A Discourse Analysis of Advertisements in English and Vietnamese on the Internet. The data for this thesis are 200 samples of advertisements on the internet (100 in English and 100 in Vietnamese). The main methods are the descriptive and contrastive analysis. English is chosen as the target language (L2) and Vietnamese serves as the source one (L1). This method helps collect the contrastive information of the advertisement in English and Vietnamese and establish the similarities and differences in terms of semiotic features. In addition, the findings of this study are clearly presented under the perspective of semiotics. The data analysis showed the discourse features of Advertisements in English and Vietnamese on the Internet in terms of the communication functions, stylistic devices and the effects of the combination of music, language and pictures in advertisements. It is hoped that the results of this study will really provide some practical applications for teaching and learning English. This thesis may also be helpful for those who are interested in advertising, especially advertisements on the internet.